Penerapan Smartfarming Berbasis IoT Pada Kelompok Tani: Kontrol Nutrisi dan Monitoring Lingkungan - Erlin Widya Fatmawati; Samudi; Titik Irawati; Fadilla Eka Wahyuni (Universitas Sunan Drajat Lamongan, Indonesia, 2026)
Purpose of this activity is to empower farmer groups through premium melon cultivation training based on Internet of Things (IoT) technology to increase agricultural productivity and efficiency. This training is carried out by integrating theory and practice of using IoT devices, such as humidity sensors, temperature and automatic irrigation control. The results of this program show an increase in farmers' knowledge and skills in utilizing technology for environmental monitoring and plant nutrition management. The significant impacts of this program include increasing productivity by up to 30%, melon quality meeting premium market standards, and reducing the risk of crop failure through early detection of problems. Apart from that, this training succeeded in encouraging farmers' independence in operating IoT devices and strengthened the competitiveness of local agriculture. However, obstacles such as initial technology costs and limited internet infrastructure are challenges that need to be overcome. It is hoped that this program can become a technology-based empowerment model for other agricultural sectors, with the potential to expand access to national and international markets. Sustainability of the program requires continued training support, development of processed melon products, and IoT-based data analysis to optimize efficient and environmentally friendly agricultural practices.